PENGARUH EDUKASI GIZI TERHADAP PENGETAHUAN DAN SIKAP ANAK SEKOLAH DASAR DALAM PEMILIHAN JAJANAN SEHAT: LITERATURE REVIEW The Eff ect of Nutrition Education on Knowledge and Attitude about Selection of Healthy Snacks among Elementary Students: Literature Review - Kus Aisya Amira; Stefania Widya Setyaningtyas (Universitas Airlangga, 2021)
Healthy snacks are snacks that are clean, safe, healthy, and nutritious. The food safety of snacks sold in school environment cannot be guaranteed, so it can cause food poisoning among children. The importance of food safety knowledge can be used to prevent food poisoning from contamination such as biological, chemical, or physical contamination. Based on several studies, healthy snacks education can improve children’s knowledge and attitudes that related to the selection of healthy snacks by using various media. The purpose of this literature review is to determine the eff ect of nutrition education on knowledge and attitudes of elementary students in the selection of healthy snacks. This literature study included the articles which used experimental study with pre-test and post-test in elementary students as the subject. There are ten selected articles that were included in the review. The results indicated that nutrition education about healthy snacks could improve knowledge of students in selecting healthy snacks. Moreover, there were 6 articles showed that nutrition education could improve the attitudes of students in the selection of healthy snacks as well. Nutrition education can infl uence the knowledge and attitudes of elementary students in the selection of healthy snacks.